Identifikasi Tingkat Kapabilitas Tata Kelola TI Menggunakan COBIT 2019 Pada KOMINFO Kota Bitung Sulawesi Utara - Cherry Lumingkewas; Joe Yuan Mambu; Andria Wahyudi (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2023)
Effective information technology governance (ITG) is vital for managing risks and ensuring proper oversight of IT in government organizations and enterprises. However, many organizations struggle with implementing effective ITG strategies, resulting in a higher likelihood of cybersecurity breaches, operational inefficiencies, and financial losses. This study addresses the urgency of improving ITG by assessing the capability level of ITG within the Ministry of Communication and Information Technology (KOMINFO) in Bitung, North Sulawesi, using the widely recognized COBIT 2019 framework. By conducting interviews with key IT personnel, the study quantifies the capability level of eleven core models and highlights areas that require improvement. The results underscore the critical importance of designing and implementing effective IT governance to mitigate risks and enhance IT oversight in government organizations and enterprises. The study's findings can serve as a foundation for future efforts to improve IT governance in KOMINFO and other organizations, ultimately contributing to a safer and more secure IT environment.